Storage of Stock Cultures of Filamentous Fungi, Yeasts, and Some Aerobic Actinomycetes in Sterile Distilled Water - McGinnis, M. R. (1974)
Castellani's procedure for maintaining cultures of filamentous fungi and yeasts in sterile distilled water was evaluated. Four hundred and seventeen isolates of 147 species belonging to 66 genera of filamentous fungi, yeasts, and aerobic actinomycetes were maintained in sterile distilled water at room temperature over periods ranging from 12 to 60 months in four independent experiments. Of the 417 cultures, 389 (93%) survived storage in sterile distilled water. The selection of good sporulating cultures and sufficient inoculum consisting of spores and hyphae suspended in sterile distilled water were the most important factors influencing survival in water over a longer period of time. The technique was found to be simple, inexpensive, and reliable.